TAX EVASION AND ITS EFFECTS ON THE IRAQI ECONOMY (REALITY AND PROCESSORS) - Suad jawad kadhim; Alaa Abbas Dakhil; Bahaa Abdel Wahab Abdel Hussein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The phenomenon of tax evasion is one of the economic problems that various developing or developed economies suffer from, with its percentage varying from one country to another. This depends on the causes and consequences of this phenomenon on the economy. And its direct impact on the state’s general budget, which is not limited to reducing the proceeds of tax revenues only. Rather, it also limits the state’s ability to perform economically and address the problems that the economy suffers as a whole. Tax evasion also leads to a misdistribution of public burdens. This study will address the nature of tax evasion and its causes in the Iraqi economy and a review of a number of mechanisms and proposed treatments for the advancement of tax systems to reduce the problem of tax evasion as it represents the second resource for financing the general budget of the Iraqi economy after oil, as the latter is characterized by the instability of its prices and thus the disparity of its revenues in the form that makes Reliance on sources of tax revenue is essential.